Observations on the Effect of Thymectomy or Chemical Carcinogenesis in the Hamster Cheek Pouch - Polliack, A. (Nature Publishing Group, 1972)
The effects of thymectomy and sham operation on 9,10-dimethyl-1,2-benzanthracene (DMBA) induced tumours of the hamster cheek pouch were studied in Syrian golden hamsters. The incidence of carcinomata and papillomata with intra-epithelial carcinoma (atypical papillomata) in these animals was compared with that in control animals treated with DMBA alone, without surgical intervention. In 32 non-operated control animals, the average tumour yield after 12 weeks' DMBA application was 2·13 carcinomata and 1·22 atypical papillomata per treated pouch. In 14 animals thymectomized at the age of 2 weeks, the tumour yield was 0·21 and 0·36, respectively, and in 10 animals thymectomized when adult, it was 0 and 0·1 respectively. In 9 animals sham operated on at the age of 2 weeks, an average of 1·56 carcinomata and 1·22 atypical papillomata were found, but in 13 animals which were sham operated when adult, the tumour yield was 0·54 and 0·15 per treated pouch, respectively. The results suggest that the time of thymectomy in relation to DMBA treatment may be of importance and that thymectomy, when performed in 2-week old hamsters, inhibits DMBA tumourigenesis. The major effect of thymectomy performed in adult hamsters appears to be related to stress following surgery.